(untitled) (Bangladesh Journal of Urology, 2020)
Penile fracture is an uncommon urological emergency, especially in Bangladesh. Theother name is traumatic rupture of the tunica albugenia and corpora cavernosa in theerect penis. It occurs when an erect penis face to buckle under the pressure of a bluntsexual trauma. Patient gives the typical history of immediate detumescence, severepain, swelling and eggplant deformity of the penile shaft due to penile injury. Immediatesurgical exploration and repair of corpora Cavernosa with tunica albugenia is the mosteffective treatment modality. In normal cases diagnosis is made from history, physicalexamination alone. In some special cases ultrasonogram, radiological images, includingretrograde urethrography or cavernosography are mandatory for proper diagnosis. Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.95-99